Educational capsules of audiovisual content for the development of listening skills in visually impaired students at Daniel Reyes High School - Gómez Suárez, Gisela Alexandra (2023)
Propose the use of educational capsules of audiovisual content platforms as a pedagogical tool to enhance the development of listening skills in a second-grade student with visual impairment at "Daniel Reyes" high school in San Antonio de Ibarra during the 2022-2023 academic year.